Pengaruh Karakteristik Pekerjaan, Motivasi Dan Disiplin Kerja Terhadap Kepuasan Kerja (Studi Pada Karyawan Kantor Kecamatan Semarang Utara) - Melisa Candra Kirana; Tristiana Rijanti (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effect of job characteristics, motivation and work discipline on job satisfaction at the Kantor Kecamatan Semarang Utara. The population of this study were all employees of the Kantor Kecamatan Semarang Utara and the sample used was 82 employees. Sampling using Random Sampling and collection methods using a questionnaire. The analysis in this study uses multiple linear regression analysis with the help of SPSS version 25. Based on the results of the study that job characteristics have a positive and significant effect on job satisfaction, motivation has a positive and significant effect on job satisfaction, and work discipline has a positive and significant effect on job satisfaction. Keyword: Job Characteristics, Motivation, Work Discipline, And Job Satisfaction.